2022
DOI: 10.3389/fphys.2022.855957
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Dietary Fish Meal with Defatted Black Soldier Fly (Hermetia illucens) Larvae Meal Affected Growth, Digestive Physiology and Muscle Quality of Tongue Sole (Cynoglossus semilaevis)

Abstract: For solving the global shortage of fish meal (FM) supplies from fisheries, the black soldier fly (Hermetia illucens) has become a new protein alternative in aquatic feeds. The present study investigated the effects of dietary inclusion of defatted H. illucens larvae meal (DBLM) on growth, serum biochemical parameters, digestive function, and muscle quality of tongue sole (Cynoglossus semilaevis). The feeding experiment consisted of five experimental diets: a control diet based on FM protein (H0) and four DBLM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Based on the study by Nya and Austin [88], ALB and GLOB contributed to a healthy system and function of plasma carriers. In addition, ALB and ALT are indicators of hepatocyte injury and liver necrosis [89]. The present findings showed that the 24.5% BSFL recorded the highest ALT compared to the other treatment groups.…”
Section: Discussionsupporting
confidence: 49%
“…Based on the study by Nya and Austin [88], ALB and GLOB contributed to a healthy system and function of plasma carriers. In addition, ALB and ALT are indicators of hepatocyte injury and liver necrosis [89]. The present findings showed that the 24.5% BSFL recorded the highest ALT compared to the other treatment groups.…”
Section: Discussionsupporting
confidence: 49%
“…It is imperative for the aquaculture industry to find substitutes for fishmeal in the feeds of farmed fishes due to decreasing natural resources and the increasing price of fishmeal. HI meal has been previously used to partially replace fishmeal in the feeds of fish species including gilthead seabream ( Sparus aurata ) ( Bosi et al., 2021 ; Randazzo et al., 2021 ), rainbow trout ( Oncorhynchus mykiss ) ( Rimoldi et al., 2019 ), tongue sole ( Cynoglossus semilaevis ) ( Li et al., 2022 ) and zebrafish ( Danio rerio ) ( Fronte et al., 2021 ). The effects of replacing fishmeal with HI meal depend on fish species and the amount of substitution.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of HI meal (up to 30%) in the diets of rainbow trout was reported to improve fish health through influencing the intestinal bacterial community ( Rimoldi et al., 2019 ). In tongue sole ( C. semilaevis ), low-level (substituting 25% of fishmeal) dietary HI meal had positive effects on growth; however, the substitution of fishmeal up to 50% resulted in a significant decrease in growth, intestinal structural damage and abnormal liver function ( Li et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies showed highest growth performance on 20% fishmeal replacement with the inclusion of 20gm BSFLM per 100gm of diet in Dusky kob fish (Madibana et al, 2020). Whereas it was 25% with the inclusion of 20.20gm and 14.41gm BSFLM per 100gm of diet in African catfish and Tongue Sole respectively (Azri et al, 2022;Li et al, 2022). Rawski et al (2020) and Aisyah et al (2022) stated that the best result of growth was found in 30% fishmeal substitution with 30gm and 19gm of BSFLM incorporation in 100gm of diet in case of sturgeon and red hybrid tilapia respectively.…”
Section: Water Qualitymentioning
confidence: 99%